Botanical authentication of globe artichoke-containing foods: Differentiation of Cynara scolymus by a novel HRM approach. (1st January 2022) - Grazina, Liliana; Batista, Andreia; Amaral, Joana S.; Costa, Joana; Mafra, Isabel
Highlights: A novel real-time PCR coupled to HRM analysis differentiated Cynara spp. The approach allowed discriminating C. scolymus from other Cynara species. C. scolymus was detected down to 0.4 pg (0.36 copies) of DNA. Application to authenticate plant food supplements and herbal infusions was shown. C. scolymus was detected in 38% of the samples, while 7% suggest mislabelling. Abstract: Cynara scolymus L., known as globe artichoke, is a medicinal plant widely used in plant food supplements (PFS) and herbal infusions due to its beneficial health properties. The high demand for artichoke-containing products can lead to adulteration practices. In this work, a real-time polymerase chain reaction (PCR) system coupled to high-resolution melting (HRM) analysis was proposed to differentiate C. scolymus from other Cynara species. Hence, a Cynara -specific real-time PCR assay was successfully developed with high analytical performance, achieving a sensitivity of 0.4 pg of globe artichoke DNA. HRM analysis enabled the discrimination of C. scolymus, with a high level of confidence (>98%), corroborating sequencing data. Application results to artichoke-containing PFS and mixed herbal infusions allowed confirming the presence of C. scolymus in 38% of the samples, suggesting the substitution/mislabelling of globe artichoke in 2 samples and the need for further efforts to increase DNA amplifiability of PFS.